Desain Pembelajaran Peluang dengan Pendekatan PMRI Menggunakan Kupon Undian untuk Siswa Kelas VII - Yanti, Welly; Hartono, Yusuf; Somakim, Somakim (Jurnal Elemen, 2016)
This research aims to determine the role of lottery coupons can help students find the concept of probability for class VII. Design Research had chose as a kind of research to achieve the goal. In this reseacrh, a series of learning activities designed and developed based on the hypothesis of the learning process of students. Learning approach used,that is, PMRI approach by involving 32 students of class VII MTs Campang Tiga. This research result Learning trajectory (LT), which contains a series of learning processes in the two activities, that is, understand the concept of sample space, sample point and the event occurrence. Results of the experiments show that with the approach of learning PMRI can define the concept of sample space and sample points and probabilities of an event by taking the lottery tickets. With the line of learning from taking lottery tickets, determine the sample space and sample point and determine the probability of occurrence can improve comprehension, reasoning students on the matters of probability.